Health-related quality of life assessed by LupusQoL questionnaire and SF-36 in Turkish patients with systemic lupus erythematosus - DİRESKENELİ, RAFİ HANER; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER LONDON LTD, 2016)
The LupusQoL is a disease-specific health-related quality of life (HRQoL) measure for patients with lupus. We conducted this study to compare the efficiency of LupusQoL-TR (validated Turkish version of the LupusQoL questionnaire) with the 36-item Short-Form Health Survey (SF-36), a generic quality of life (QoL) scale, in Turkish patients with lupus. Both questionnaires were conducted at a single visit to the clinic. Disease activity was measured with the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Associations between the LupusQoL-TR and SF-36 domains were examined while also examining age, disease duration, and disease activity for each questionnaire. Descriptive statistics, Spearman's correlation coefficients, and Students t test were performed to analyze the data. A total of 113 consecutive patients with lupus (F/M 108:5, mean age 40.6 +/- 11.9 years, mean disease duration 8.5 +/- 7.0 years) were included, and 69 % of these were active. The median SLEDAI score was 2 (0-24), the mean global LupusQoL-TR score was 60.9 +/- 23.3, and the mean SF-36 score was 41.2 +/- 9.0. There was a significant correlation between LupusQoL-TR and SF-36 mean scores (r = 0.83; p < 0.001). QoL assessed by LupusQoL-TR and SF-36 did not correlate with disease activity (r = -0.11; p = 0.244 and r = -0.03; p = 0.721, respectively). LupusQoL-TR and SF-36 questionnaires were beneficial instruments in evaluating HRQoL in Turkish lupus patients. However, LupusQoL-TR and SF-36 were not associated with SLEDAI scores, which suggested that QoL might be affected by other factors besides disease activity, especially in clinically inactive or mildly active patients.
Keywords: LupusQoL-TR; Quality of life; SF-36; Systemic lupus erythematosus; DISEASE-ACTIVITY; VALIDATION; IMPACT; SLE